Protecting the individual from international authority human rights in international organizations - Heupel, Monika 1975-; Zürn, Michael 1959- (Cambridge University Press, 2017)
"International organizations (IOs) develop institutional provisions to make sure that their policies do not violate human rights. Accordingly, whilst IOs have a greater scope of action and ability to promote collective goods than ever before, they also have a greater capacity to do harm. Based on ten case studies on UN and EU sanctions policy, UN and NATO peacekeeping, and World Bank and IMF lending, this book examines human rights violations which can arise from the actions of IOs rather than those of states. It further explains how powerful IOs have introduced human rights protection provisions and analyzes the features of these provisions, including differences in their design and quality. This book provides evidence of a novel legitimation strategy authoritative IOs draw on that has, as yet, never been systematically studied before." -- Book description
Auf dem Cover: "Edited by Monika Heupel and Michael Zürn"
Keywords: Menschenrecht; Recht; International agencies; Human rights; International agencies -- Law and legislation; Liability for human rights violations; Tort liability of international agencies; International law and human rights; Menschenrechtsverletzung; Internationale Organisation; Aufsatzsammlung